The Economic Benefits of Malaysian University Degrees - Mohd Arshad, Mohd Nahar; Baharuddin, Nur Nadhira (IIUM Journal of Educational Studies, 2020)
Abstract This study analyzes the net returns of educational investment in Malaysia using the net present value approach. The estimations consider the tuition payments of nine different bachelor degree programs of public and private universities in Malaysia and the forgone earnings while undertaking the degree programs as the cost of investments in human capital. The returns to education investment are based on the expected income accrued by the individual over the employment period until retirement. Under the assumptions that an individual would work until the retirement age of 60 years and a discount rate of 4 percent, the estimations show that holding a computer science degree from Universiti Sains Malaysia would give the highest net present value. Holding a medical degree, in general, would give the lowest net returns on educational investment as compared to the other selected programs. The net returns are sensitive to the costs of education, earnings and the duration of undertaking the degree programs. Keywords: Human capital investment, net present value, private rate of return, educational investment, Malaysian degree programmes